Answer:
f(g(5)) = 64
g(f(5)) = 28
Step-by-step explanation:
Given that f(x) = x^2 and g(x) = x+3
f(g(x) = f(x+3)
f(x+3) = (x+3)^2
f(g(x)) = (x+3)^2
f(g(5)) = (5+3)^2
f(g(5)) = 8^2
f(g(5)) = 64
b) g(f(x)) = g(x^2)
g(f(x)) = x^2 + 3
g(f(5)) = 5^2 +3
g(f(5)) = 25 + 3
g(f(5)) = 28
Hence the value of g(f(5)) is 28
3 * -12 - 17 =
3 * -12 = -36
-36 - 17 = -53
Answer = A
Answer:
14.52
Step-by-step explanation:
13.57 + 13.57 x 7% = 13.57 x (1+7/100) =13.57 x 107/100 = 14.52
Answer:
1/12 (or 0.833)
Step-by-step explanation:
Recall that the definition of "slope" is the change in vertical distance divided by the change in the horizontal distance. (aka. rise ÷ run)
it is given that rise = 50 feet and the horizontal distance (i.,e "run") = 600feet
hence slope = rise / run = 50 / 600 = 1/12 (or 0.833)